High speed rail transport valuation and policy decisions - Pimentel, Pedro (2008)
The present paper investigates the process of decision making regarding the optimal timing to invest in the high speed rail (HSR) project, under uncertainty, using the real options analysis (ROA) framework. It’s developed a continuous time framework that allows a solution to the problem concerning the optimal timing to invest and to value the impact of the option to defer in the overall valuation of the project, with multiple uncertainty factors. Besides considering a stochastic demand, the effect of uncertainty in the investment’s expenditure and over the benefit per user is incorporated in a model with three stochastic variables. The modelling approach used is based on the differential utility provided to railway users by the HSR service.